Do Chinese-focused U.S. listed SPACs perform better than others do? - Gimede Gigante; Giovanni Maria Guidotti (Investment Management & Financial Innovations, 2021)
The extraordinary growth of China from the early 2000s until now made it one of the biggest economies in the world. Over the years, more and more Chinese companies merged with the U.S. listed special purpose acquisition companies (“SPACs”) to become public and attract foreign capital. This paper examines the differences between this specific subsample of SPACs focused on completing a merger with a business located in China among those listed on the U.S. Stock Exchanges and the other U.S. listed SPACs. The intent is to verify whether the sample differs from the rest of the market in their main characteristics, have better, equal, or worse prospects of completing a merger, and offer better, equal, or worse returns to investors. 329 SPACs were identified, of which 41 targeting Chinese businesses. Logistic regression is performed to understand whether the China market focus influences the chances of consuming a business combination. Moreover, two different models (event study approach and buy-and-hold approach) are implemented to assess the share performances of the two subsamples. The conclusions that stem from the obtained results are that China-focused SPACs differ consistently from the rest of the market in certain features but need similar time to identify a target and close the deal. Focusing on China seems to be beneficial for the SPAC’s prospects of closing a deal, being statistically significant at a 10% level. Last, a portfolio composed of the sample SPACs’ shares overperforms the non-China one in both the short and long terms. Acknowledgment The authors would like to thank their brilliant student, Mr. Daniele Notarnicola, for the precious support given during the review of the paper.